Carotid artery intima media thickness in relation with atherosclerotic risk factors in patients with newly diagnosed type 2 diabetes mellitus in a rural tertiary care hospital in central India - Verma, Vijay Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Vascular complications of atherosclerosis are major causes of morbidity and mortality in patients with type 2 diabetes mellitus (T2DM). The aim of the study was to study the correlation between carotid artery intima media thickness (CIMT) and risk factors for atherosclerosis and atherosclerotic vascular events in newly diagnosed type 2 diabetes mellitus patients with an objective to determine the predictive value of CIMT as an indicator of early atherosclerosis. Methods: The predictive value of CIMT as well as various atherosclerotic risk factors including ankle brachial index (ABI) were determined as an indicator of early atherosclerosis. Data were presented in form of percentage and proportions. Qualitative variables were tested using Chi square test and the p values were calculated between the groups having CIMT less than and more than 0.9 mm. p values of ≤0.05 were considered statistically significant. Averages were expressed between groups as mean ±standard deviation or as percentage. Multivariate analysis was done using the multiple linear regression model. Results: The study showed that though age, smoking and dyslipidemia did not show any association with CIMT; hypertension, ABI, glycosylated hemoglobin and urine albumin excretion rate had positive correlation with CIMT with statistically significant association between ABI and CIMT. Conclusions: Assessment of CIMT by B mode ultrasound is a relatively inexpensive means of measuring subclinical atherosclerosis. Present study showed that CIMT is significantly higher in those type 2 diabetic patients who had atherosclerotic events than in those type 2 diabetic patients who had only risk factors for atherosclerosis.